Delik Aduan Tindak Pidana Perzinahan dalam Pandangan Hukum Pidana dan Hukum Islam - Sirajuddin Sirajuddin; Risdayani Risdayani; Dewi Indriani (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This research is driven by the recognition that adultery represents a criminal offence that challenges the values of decency and social order, and has the potential to have adverse implications for individuals, families, and society at large. The objective of this research is to examine the provisions pertaining to complaints filed by victims of adultery, with a particular focus on the comparison between Indonesian national criminal law and Islamic law (fikih jinayat). The research employs a qualitative approach with a normative focus, utilising an inductive analysis of data gathered from legal literature. The findings indicate that Islamic law offers greater latitude in filing complaints of adultery, extending to both victims of adultery crimes and those who have suffered harm. Additionally, it imposes more severe penalties. In contrast, national criminal law prioritizes the protection of victims' rights, while also providing for the mitigation of punishment for the family of the perpetrator of adultery crimes. The findings of this research demonstrate the necessity for a comprehensive understanding of the distinctions between these two legal systems to develop a national criminal law that aligns with Islamic law in the enforcement of adultery laws.